PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR LURAH LAWANG KIDUL KOTA PALEMBANG - Salman .; Agustina Marzuki (Fakultas Ekonomi Universitas Tridinanti Palembang, 2018)
This study was conducted at the Office of Lawang Kidul urban village of Palembang, the number of employees as many as 31 people and entirely sampled. The result of regression between Leadership (X1), Motivation (X2) and Discipline (X3) to Performance (Y) variable is 20,782, stated that if there is no increase of Leadership (X1), Motivation (X2) and variable Discipline (X3) on Performance (Y) then the value of performance of 20.782. The regression coefficient of 0.319, 0.185 and 0.202 states that each addition of a score of Leadership (X1), Motivation (X2) and Discipline (X3) variables will give a score increase of 0.319, 0.185 and 0.202 for Performance (Y) so that the form of multiple regression equation are as follows : Y = 20.782 + 0.319 X1 + 0.185 X2 + 0.202 X3. Correlation between variables Leadership (X1), variable Motivation (X2) variable Discipline (X3) with variable Performance (Y) obtained R value of 0.628. The acquisition value of correlation coefficient (R) means that if the Leadership variable (X1), Motivation Variable (X2) and Discipline variable (X3) have a very close relationship to Performance (Y). Coefficient of determination equal to 0,394 or 39,4%. Coefficient of determination used to know the percentage of influence of independent variables (Predictors) to changes in the dependent variable. From the processed processed data obtained value of determinant coefficient of 0.394. This means that the contribution of leadership variables, motivation and discipline to performance variables is 39.4% while the remaining 60.6% is influenced by other variables not examined in this study. Keywords: Leadership style, Motivation and work discipline